2022
DOI: 10.1093/ajcn/nqab419
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation and prevention of cardiovascular disease and cancer in the Finnish Vitamin D Trial: a randomized controlled trial

Abstract: Background Vitamin D insufficiency is associated with risk of cardiovascular diseases (CVD) and cancer in observational studies, but evidence for benefits with vitamin D supplementation is limited. Objectives To investigate the effects of vitamin D3 supplementation on CVD and cancer incidence. Design The study was a 5-year randomized placebo-controlled trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 21 publications
1
37
0
1
Order By: Relevance
“…Furthermore, adherence to the interventions was high, with on average above 80% for the study medication and on average over 60% for performing the exercise program at least twice a week ( Bischoff-Ferrari et al, 2020 ). Furthermore, the rate of any new invasive cancer in DO-HEALTH participants aged 70 and older was representative for the age-group investigated ( White et al, 2014 ), between 3.8% (81 verified cases) and 5.2% (113 reported cases), compared with 1.2% in VITAL participants aged 50 years and older and a little less compared to the Finnish Vitamin D Trial with 5.2% (129 recorded cases) in participants aged ≥60 years ( Virtanen et al, 2022 ). Finally, the consistency of findings between the primary analysis and sensitivity analyses lends strength to our findings.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, adherence to the interventions was high, with on average above 80% for the study medication and on average over 60% for performing the exercise program at least twice a week ( Bischoff-Ferrari et al, 2020 ). Furthermore, the rate of any new invasive cancer in DO-HEALTH participants aged 70 and older was representative for the age-group investigated ( White et al, 2014 ), between 3.8% (81 verified cases) and 5.2% (113 reported cases), compared with 1.2% in VITAL participants aged 50 years and older and a little less compared to the Finnish Vitamin D Trial with 5.2% (129 recorded cases) in participants aged ≥60 years ( Virtanen et al, 2022 ). Finally, the consistency of findings between the primary analysis and sensitivity analyses lends strength to our findings.…”
Section: Discussionmentioning
confidence: 90%
“…For vitamin D and cancer prevention, our trial tested a daily dose of 2000 IU vitamin D 3 , which according to a recent meta-analysis on cancer prevention, may have reduced cancer death on its own ( Keum et al, 2019 ), while an effect of Vitamin D on cancer incidence was not seen, neither in the 5-year Finnish Vitamin D Trial, where 1600 IU/d and 3200 IU/d were tested against placebo in 2,495 participants ≥60 years ( Virtanen et al, 2022 ), and the meta-analysis by Keum et al This meta-analysis evaluated ten RCTs (6,537 cases) and included the large VITAL trial ( Manson et al, 2019b ). Four of the included trials provided a large intermittent bolus of vitamin D 3 (20,000 IU/week–500,000 IU/year), and six trials provided vitamin D 3 in a daily dose (400–2000 IU/day) ( Keum et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 11 RCTs with a total of 51,369 participants were included in the meta-analysis for cancer incidence [ 14 , 30 , 32 , 34 , 35 , 37 , 38 , 41 , 42 , 43 , 45 , 46 ]. No significant association of vitamin D supplementation with overall cancer incidence was found (RR 0.99, 95% CI 0.93–1.06, I 2 = 0%; Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…While this would support population-wide vitamin D supplementation to eradicate vitamin D deficiency, results from recent large randomized controlled trials (RCTs) are not supportive. VITAL trial, ViDA study and FIND trial found supplemental vitamin D not to be beneficial to reduce major cardiovascular events [26] , [27] , [28] . This was most probably due to an inadequate number of participants with very low vitamin D levels which would not permit detection of beneficial effects for relatively rare disease endpoints such as cardiovascular events.…”
Section: Discussionmentioning
confidence: 98%